Мікробіологічний моніторинг патогенної мікробіоти слизових оболонок очей страусів африканських (Struthio camelus) - Передерко, Леся; Perederko, Lesya (Східноєвропейський національний університет імені Лесі Українки, 2014)
Проведено мікробіологічний моніторинг патогенної мікробіоти слизових оболонок очей страусів афри¬канських (Struthio camelus), які утримуються при інтенсивній системі у природних ареалах західних областей України. Для підрахунку загального мікробного числа використовували м’ясо-пептонний агар і бульйон (МПА і МПБ), для виявлення ентеробактерій – середовище Плоскірева і Левіна. Під час моніторингу патогенної мікробіоти кон’юнктиви очей страусів африканських (Struthio camelus) виділено від 20 до 50 тис. грам-нега¬тивних коків та близько 500 тис. грам-позитивних мікроорганізмів. To improve the adaptive quality of synanthrope species to environmental factors temperate continental climate of Western Ukraine was monitoring a pathogenic microbiota of eye conjunctiva of African ostrich (Struthio camelus). The study was conducted at the Research Laboratory of Molecular Microbiology and Immunology of the mucous membranes in the Uzhgorod National University. Sowing research material was performed by seeding directly on the dish with the appropriate nutrient environment and seeding diluted. All samples were seeded on classical modern (chromogenic) and differential diagnostic culture environment. Meat peptonnyy agar and broth (MPA and MPB) were using to calculate the total microbial count, environments Ploskiryev and Levin – for detection of Enterobacteriaceae. Environments Endo, agar Klihlera, enterococ and streptococ agars, URI Select agar, egg-salt agar (ESA), blood agar (BA) and bismuth-sulfite agar (BSA); tests for acetate, citrate, mannitol, lactose, glucose, catalase and phenylalanine, OXI and INDOL tests, serological tests Latex- Staph+, Strep+ esherihiozni and diagnostic serum were used as storage, selective and differential diagnostic. Biochemical semiautomatic test systems: API, Enter 24, Anaero 23, Kandy and Enterococc were used for identification. During the monitoring of pathogenic microbiota of mucous membranes of eyes of Struthio camelus were isolated from 20 to 50 thousand Gram-negative cocci and about 500 thousand gram-positive microorganisms. Among isolates in natural landscape zone of Carpathian region the highest degree of microbial contamination were large groups of microorganisms mucous with jagged edges and shiny surface of Gram-negative cocci colony of Klebsiella pneumonia. In other two samples Escherichia coli and Klebsiella pneumonia were allocated which make up the same proportion of colony forming units. Groups of Gram-negative cocci of Escherichia coli were small slimy colonies with smooth edges and a shiny smooth surface. Microbiological monitoring in the other two habitats was allocated only isolates of Staphylococcus aureus − gram-positive cocci, which grew as a small gray-yellow colonies round shape with a shiny surface.
Microbiological Monitoring of Pathogenic Microbiota of Mucous Membranes of Eyes of African Ostriches (Struthio camelus)
Keywords: Struthio camelus; мікробіота; моніторинг; Klebsiella pneumoniae; Escherichia coli; Staphylococcus aureus; Struthio camelus; microbiota; monitoring; Klebsiella pneumoniae; Escherichia coli; Staphylococcus aureus